2012
DOI: 10.5032/jae.2012.04070
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Agricultural Experience: An Examination of Student Knowledge and Participation

Abstract: The purpose of this study was to investigate student Supervised Agricultural Experience (SAE) knowledge and participation. This descriptive study was conducted in 120 randomly selected agricultural education programs throughout four purposively selected states representative of the National FFA regions. Students completed a questionnaire assessing knowledge of the five SAE categories. According to findings of this study, 46.1% of the students surveyed reported having a SAE program (n = 473). Students on averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Findings indicated a majority of respondents did not lead programs aligning with their ideal programs, reducing the likelihood that teachers lead SAE Light programs due to a lack of perceived value in SAE. Other studies have reported the value teachers hold in SAE programs (Lewis et al, 2012), further supporting the notion that teachers want to emphasize SAEs, but have not been successful in doing so. This disparity between current and ideal program was found both within and outside of the millennial generation.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 85%
See 2 more Smart Citations
“…Findings indicated a majority of respondents did not lead programs aligning with their ideal programs, reducing the likelihood that teachers lead SAE Light programs due to a lack of perceived value in SAE. Other studies have reported the value teachers hold in SAE programs (Lewis et al, 2012), further supporting the notion that teachers want to emphasize SAEs, but have not been successful in doing so. This disparity between current and ideal program was found both within and outside of the millennial generation.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 85%
“…Researchers have documented a decline in students' and teachers' development and maintenance of SAEs over the past 30 years (Barrick, Hughes, & Baker, 1991;Dyer & Osborne, 1995;Dyer & Williams, 1997;Retallick & Martin, 2008;Rubenstein & Thoron, 2014). Despite the decline in participation, research has consistently reported the benefits of SAEs on knowledge acquisition (Arrington & Cheek, 1990;Pals, 1988;Ramsey, 2009;Williams, 1979) and on teachers' high value of SAEs (Lewis, Rayfield, & Moore, 2012;Robinson & Haynes, 2011).…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a decline in student participation in SAEs at the secondary level exists (Croom, 2008). Although the reasons for the decline are largely unknown (Bird, Martin, & Simonsen, 2013), it could be due to teachers' lack of knowledge of and experience in SAEs (Lewis, Rayfield, & Moore, 2012).…”
Section: )mentioning
confidence: 99%
“…In the early 1990's, over 85% of agricultural education students in Iowa conducted SAEs, by 2005, that number dropped to only 56% (Retallick & Martin, 2008). More recently, an average of 46% of students surveyed in Florida, Indiana, Missouri, and Utah reported conducting an SAE (Lewis, Rayfield, & Moore, 2012). Although participation has declined, agricultural educators across the country agree that SAE is and should remain an integral component of school-based agricultural education (Camp et al, 2000;Wilson & Moore, 2007) due to a myriad of beneficial outcomes for students.…”
Section: Introductionmentioning
confidence: 99%